Seasonal Variations in Odonata Assemblages: A Comparative Study of Rural and Urban Agroecosystems in Gaya, Bihar - ShehaKumari Bharati; A. Pattanayak; S.N.P Yadav Deen (The Bioscan, 2025)
This study investigates the diversity, abundance, and seasonal variation of Odonata (dragonflies and damselflies) in rural and urban agroecosystems in Gaya district, Bihar, India. Data were collected from Manpur (rural) and Gaya urban belts, revealing distinct patterns in Odonata assemblages influenced by habitat type, seasonal factors, and environmental variables. A total of 16 Odonata species across three families (Aeshnida, Libellulidae, and Coenagrionidae) were recorded in Manpur, whereas only nine species were documented in Gaya urban. The Shannon diversity index (H) was significantly higher in Manpur (2.85) than in Gaya urban (2.1), indicating greater species richness and evenness in the rural ecosystem. Community composition differed notably between the sites: Anisoptera (dragonflies) dominated in Manpur (77% of the assemblage), while Zygoptera (damselflies) were more abundant in Gaya urban (75%). Exclusive species were observed at both sites, with Anaciaeschnajaspidea, Neurothemisfulvia, and Rhodothemisrufa recorded only in Manpur, and Anaxguttatusand Brachydiplaxchalybea unique to Gaya urban. Family-level analysis showed Libellulidae as the most dominant family at both sites, with relative abundances of 74.1% (Manpur) and 74.0% (Gaya urban). Coenagrionidae had a slightly higher abundance in rural areas (25.2%) compared to urban areas (22.9%). Seasonal patterns revealed that Odonata abundance peaked during the monsoon season in both ecosystems, with key species such as Pantalaflavescens and Orthetrumsabina showing significant increases in population during this period. Statistical analysis using ANOVA and Kruskal-Wallis tests revealed significant seasonal variations in Odonata abundance in Manpur (p < 0.001), underscoring the influence of climatic factors on species dynamics. This study highlights the greater ecological stability and diversity in rural agroecosystems compared to urban areas and emphasizes the need for conservation strategies tailored to habitat-specific dynamics.